INFORMATION SUSTAINABILITY OF ISLAMIC EDUCATION CENTERS THROUGH WEBSITE DIGITIZATION - Nurhasana, Renny; Muhafilah, Nurul; Kasih, Nur Arning Tengara (UI Scholars Hub, 2022)
Islamic education of Taman Pendidikan Al-Quran (TPA) is an Al-Quran Learning Center that gives informal religious education to guide children to know Islamic values from an early age. TPA Ikhlasul Machfudz was established since 2006 that, in addition to Al-Quran, the center also teaches children with English, Marawis (voices with strong religious elements) and Qasidah (lyrics that are related to Islamic values). However, since the COVID-19 pandemic occurred in 2020, the learning process has stopped completely due to the policy of learning from home. There are many obstacles to teach from home using online learning method. Teachers realized the importance of website and other digitization process to help for information sustainability and learning process. Websites are also important as a platform to document information and promote TPA Ikhlasul Machfudz to a wider audience. This community service activity was carried out by academicians who helped in several stages, namely website creation, website usage training, and website inauguration. All activities were carried out using online coordination. Data analysis was performed using qualitative method in coordination with key informant by observation, interviews, and documentation. With this website digitization, teachers and guardians of students found that this process is valuable and helpful for the learning progress during the pandemic. The center also further benefited because the website usage, at the same time, can be a place for documenting various activities and maintaining the information sustainability. The existence of this website expected to help facilitate the teaching and learning process in the future. Taman Pendidikan Al-Quran Ikhlasul Machfudz (TPA-IM) can also maintain the information sustainability as an informal community organization in Lenteng Agung, South Jakarta.